Healthcare Options for People Experiencing Depression (HOPE*D): the development and pilot testing of an encounter-based decision aid for use in primary care - Barr, Paul J (BMJ Open, 2019)
OBJECTIVE: To develop and pilot an encounter-based decision aid (eDA) for people with depression for use in primary care. DESIGN: We developed an eDA for depression through cognitive interviews and pilot tested it using a one-group pretest, post-test design in primary care. Feasibility, fidelity of eDA use and acceptability were assessed using recruitment rates and semistructured interviews with patients, medical assistants and clinicians. Treatment choice and shared decision-making (SDM) were also assessed. SETTING: Interviews with adult patients and the public were conducted in a mall and library in Grafton County, New Hampshire, while clinician interviews took place by phone or at the clinician’s office. Pilot testing occurred in a New Hampshire primary care practice. PARTICIPANTS: Cognitive interviews were conducted with adults, ≥18 years, who could read English from the following stakeholder groups: history of depression, the public and clinicians. Patients with a Patient Health Questionnaire-9 score of ≥5 were recruited for piloting. RESULTS: Three stages of cognitive interviews were conducted (n=28). Changes to eDA included moving the combination therapy information and access to treatment information, adding colour, modifying pictograms and editing the talk-therapy description. Clinician concerns about patient health literacy were not reflected in patient interviews. Of 59 patients who reviewed study information, 56 were eligible and agreed to participate in pilot testing; however, only 29 could be reached for follow-up. The eDA was widely accepted, though clinicians did not always use it as intended. We found no impact of eDA use on SDM, though patients chose a wider range of treatment options. CONCLUSIONS: We demonstrated the feasibility of the use of an eDA for depression in primary care that was widely accepted. Further research is needed to improve the fidelity with which the eDA is used and to assess its impact on SDM and related health outcomes.